2018
DOI: 10.1002/jbt.22041
|View full text |Cite
|
Sign up to set email alerts
|

The in vivo effects of cefazolin, cefuroxime, and cefoperazon on the carbonic anhydrase in different rat tissues

Abstract: In this paper, the in vivo effects of some antibiotics including cefazolin, cefuroxime, and cefoperazon, on the activity of the carbonic anhydrase enzyme (CA) in heart, brain, eye, liver, and kidney tissues of rats were evaluated. For this purpose, 16 different groups, which each containing six rats (n = 6), were formed (control group, cefazolin groups, cefuroxime groups, and cefoperazon groups). The rats were necropsied 60 min after the intraperitoneal injection of the chemicals into the rats. The CA activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 68 publications
0
27
0
Order By: Relevance
“…The reaction was also started by adding 50 μL BChI/AChI. The activity of these enzymes was evaluated using spectrophotometric spectra with a wavelength of 412 nm …”
Section: Methodsmentioning
confidence: 99%
“…The reaction was also started by adding 50 μL BChI/AChI. The activity of these enzymes was evaluated using spectrophotometric spectra with a wavelength of 412 nm …”
Section: Methodsmentioning
confidence: 99%
“…This enzyme has great importance for hydrolysis choline esters in the cholinergic synapses of the nervous system, central nervous system, and somatic system. BChE, which is a nonspecific ChE, is found in the blood plasma and serum, pancreas, heart, central nervous system, and liver of vertebrates . BChE hydrolyzes choline esters and different esters.…”
Section: Introductionmentioning
confidence: 99%
“…Voriconazole is an antifungal medication used to treat a number of fungal infections, and its inhibitory effects against some metabolic enzymes are shown in Table and Figures . Previous research has clearly indicated that the inhibitory effect of Voriconazole against hCA I, hCA II, AChE, and α‐glycosidase is greater than or equal to that of morphine, antioxidant phenols, hydroquinone, taxifolin, spirobisnaphthalenes, caffeic acid phenethyl ester, rosmarinic acid, some hydroperoxides, alcohols and acetates, some ureas, eugenol derivatives, lignans, thioureas, flavonoids, synephrine and phenylephrine, avermectins, antibiotics, and TAC derivatives . The present study adds to this previous literature (Table ).…”
Section: Discussionmentioning
confidence: 99%